An analysis of AERONET aerosol absorption properties and classifications representative of aerosol source regions ... - Giles, D. M.; Holben, B. N.; Eck, Thomas; Sinyuk, A.; Smirnov, A.; Slutsker, I.; Dickerson, R. R.; Thompson, A. M.; Schafer, J. S. (AGU, 2012)
Partitioning of mineral dust, pollution, smoke, and mixtures using remote sensing techniques can help improve accuracy of satellite retrievals and assessments of the aerosol radiative impact on climate. Spectral aerosol optical depth (?) and single scattering albedo (?o) from Aerosol Robotic Network (AERONET) measurements are used to form absorption (i.e., ?o and absorption Ångström exponent (?abs)) and size (i.e., extinction Ångström exponent (?ext) and fine mode fraction of ?) relationships to infer dominant aerosol types. Using the long-term AERONET data set (1999–2010), 19 sites are grouped by aerosol type based on known source regions to (1) determine the average?o and ?abs at each site (expanding upon previous work), (2) perform a sensitivity study on ?abs by varying the spectral ?o, and (3) test the ability of each absorption and size relationship to distinguish aerosol types. The spectral ?o averages indicate slightly more aerosol absorption (i.e., a 0.0 < ??o ? 0.02 decrease) than in previous ...